Lightweight structural eco-mortars made with polyurethane wastes and non-Ionic surfactants. (10th February 2019) - Arroyo, R.; Horgnies, M.; Junco, C.; Rodríguez, A.; Calderón, V.
Highlights: New structural lightweight mortars are obtained with substitution of sand by polyurethane wastes. Mortar with very hydrophilic surfactant almost double compressive strength with a replaced of 100% of arid by PU wastes. Additive showing higher HLB reduce the density until almost 56% and increase greatly entrained air. Mortars have very homogeneous microstructure and good adhesion between PU and cement paste. Abstract: The properties of structural lightweight mortars obtained with recovered foam polyurethane wastes have been studied, containing a low fraction of soluble non-ionic surfactant. The characterisation of mechanical properties, bulk density, microstructure and porosity highlights two types of behaviour according to the composition (e.g. hydrolysis grade) of the non-ionic surfactants. By using additives with low hydrophilic–lipophilic balance (HLB) values, the lightweight mortars show more and more high mechanical properties according to the increase of the substitution rate of sand by PU wastes. These non-ionic surfactants seem to promote a homogeneous microstructure and improve the adhesion between PU wastes and cement paste. On the other hand, the mortars mixed with additives showing high HLB values, are more lightweight and macroporous, due to the increase of air entrained driven by the substitution rate of sand by PU wastes.